ANALISIS KARAKTERISTIK PARKIR KENDARAAN BERMOTOR - Bambang Tripoli; Rahmat Djamaluddin (Universitas Teuku Umar, 2019)
Parking problems are very important to study more deeply, because almost all activities in the open space require parking facilities. The required parking space must be adequately available. On street parking is parking that takes place along the road. This has a negative impact on the smooth flow of traffic, because it causes a reduction in the width of the road being traversed. The aim of the study was to determine the characteristics of motorized parking and the shape of parking angle patterns by considering the occurrence of side barriers. The research was carried out on the Singgah Mata I Road in Kuta Padang Village, West Aceh Regency, for 3 days Monday, Thursday and Sunday from 07.00-09.00 WIB, 11.00-13.00 WIB until 15.00-17.00 WIB. The data needed in the primary data research by direct survey in the research location, including side barriers survey, parking vehicle and road geometric. Data on the number of parking vehicles were analyzed to obtain parking characteristics, parking angle and side barriers. The highest peak fluctuations occur at 4:00 a.m. to 5:00 p.m., with evidenced parking capacity and HV vehicle parking time as much as 321 pcu/hour going on Monday, while the LV, MC and MT vehicles have the highest fluctuations on Sunday, which is detailed (LV 1519 pcu/hour) , (MC 600 pcu/hour) and (MT 311 pcu/hour). Based on this, the parking area of the vehicle's average daily peak volume is LV 1084 pcu/hour, HV 225 pcu/hour, MC 412 pcu/hour and for MT vehicles is 217 pcu/hour, able to accommodate the available parking volume, every point-point of the research location with parking index value <100%, which means that demand can still be fulfilled / still able to accommodate every vehicle parked with a parking angle of 300. The highest peak of side barriers occurs on Sunday 529 occurrence of side barriers which are evidenced by the condition of the commercial area with the second activity high side of the road. Keywords: on street parking, characteristics, parking impact.